Prosthodontic Management of Flabby Ridge with a Modified Window Impression Technique – A Case Report - Eswaran.B; Rohit.M; Soniya.H (Institute of Medico-legal Publications Pvt Ltd, 2021)
The performance of a complete denture is often a reflection of its support and retention of the underlyinghard and soft tissues. If the superficial aspect of alveolar ridge is compressible more than 2mm, this willresult in a mobile soft tissue (flabby tissues). This occurs when hyperplastic soft tissue replaces the alveolarbone. During conventional impression procedures, the flabby tissues are compressed and will later tendto recoil and dislodge the resulting overlying denture. This article aims to presents a case report for theprosthodontic rehabilitation of a patient with a flabby tissue with a modified window impression technique.